Crimea versus Karshmir: a comperative overview - Usmani Muhammad Wali Ur, Rehman (Східноєвропейський національний університет імені Лесі Українки, 2020)
World is changing rapidly, but few conflicts are standing still for decades. Kashmir dispute is a clear example, which is unresolved for about 70 years now. Another territorial dispute is Crimea, which is now bleeding for more than 5 years. Due to several similarities “the Kashmir conflict” could be taken as a case study to understand the behavior of international politics on such territorial disputes. “Is Crimea going to be a Kashmir of Europe?” What is the essence of constant obstacles of Kashmir dispute that can reflect in Crimea also? What are the objectives and geopolitical importance of these disputes, what do aggressor forces claim and what is the reality behind several narratives? These question and similarities between Crimea and Kashmir issues are attempted to be highlighted in this paper. Historical development of core conflicts is focused in the overview, as it is extremely important for students of international politics to learn lesson from similar examples available. Solutions of basic problems are answered in conclusion.
Крим і Кашмір: порівняльний аналіз
Keywords: Crimea; Ukraine; Pakistan; Dispute; Kashmir; Geopolitical; Freedom; Movement; Nuclear; Political; United nations